Risk Analysis of Work Posture in Manual Welding Activities Using The Workplace Ergonomic Risk Assessment Method at UD. Inti Tekindo - Dewi Hartati; A.Amri; Cut Ita Erliana (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
Manual welding activities at UD. Inti Teknindo are carried out with work postures that are not very ergonomic, such as bending over, squatting, and leaning down for long periods, which can potentially cause musculoskeletal disorders (MSDs). This study aims to determine the risk level of welding workers' postures using the Workplace Ergonomic Risk Assessment (WERA) method and to provide improvement suggestions to reduce the risk of MSDs. The study was conducted on 4 welding workers using observation, documentation, interviews, the Nordic Body Map (NBM) questionnaire, and anthropometric measurements. The NBM questionnaire results showed that all workers were at high-risk levels with scores of 71–73, indicating complaints in the back, waist, neck, shoulders, and wrists. The analysis using the WERA method showed that worker 1 scored 45, worker 2 scored 45, worker 3 scored 45, and worker 4 scored 44, so all workers fall into the high-risk category and need corrective action. Based on this analysis, a work facility in the form of an Adjustable Welding Support Stand is proposed, designed according to the workers' anthropometric data with a stand height of 97.37–101.62 cm and a work area width of 44.3 cm. The evaluation results of the proposed design show the WERA score dropped to 27, which falls into the low-risk category. Therefore, this proposed work facility can improve working posture, reduce the risk of MSDs, and increase comfort and safety for welding workers at UD. Inti Teknindo.